Genotyping of Methicillin Resistant Staphylococcus aureus Strains Isolated from Hospitalized Children - Mouna Ben Nejma; Abderrahmen Merghni; Maha Mastouri (Hindawi Limited, 2014)
Community associated methicillin resistant Staphylococcus aureus (CA-MRSA) is an emerging pathogen increasingly reported to cause skin and soft tissue infections for children. The emergence of highly virulencet CA-MRSA strains in the immunodeficiency of young children seemed to be the basic explanation of the increased incidence of CA-MRSA infections among this population. The subjects of this study were 8 patients hospitalized in the Pediatric Department at the University Hospital of Monastir. The patients were young children (aged from 12 days to 18 months) who were suffering from MRSA skin infections; two of them had the infections within 72 h of their admission. The isolates were classified as community isolates as they all carried the staphylococcal cassette chromosome mec (SCCmec) IV and pvl genes. Epidemiological techniques, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST), were applied to investigate CA-MRSA strains. Analysis of molecular data revealed that MRSA strains were related according to PFGE patterns and they belonged to a single clone ST80. Antimicrobial susceptibility tests showed that all strains were resistant to kanamycin and 2 strains were resistant to erythromycin.